Ultrafast molecular dynamics of dissociative ionization in OCS probed by soft x-ray synchrotron radiation. (17th October 2016) - Ramadhan, Ali; Wales, Benji; Karimi, Reza; Gauthier, Isabelle; MacDonald, Michael; Zuin, Lucia; Sanderson, Joe
Abstract: Soft x-rays (90–173 eV) from the 3rd generation Canadian Light Source have been used in conjunction with a multi coincidence time and position sensitive detection apparatus to observe the dissociative ionization of OCS. By varying the x-ray energy we can compare dynamics from direct and Auger ionization processes, and access ionization channels which result in two or three body breakup, from 2+ to 4+ ionization states. We make several new observations for the 3+ state such as kinetic energy release limited by photon energy, and using Dalitz plots we can see evidence of timescale effects between the direct and Auger ionization process for the first time. Finally, using Dalitz plots for OCS 4+ we observe for the first time that breakup involving an O 2+ ion can only proceed from out of equilibrium nuclear arrangement for S(2p) Auger ionization.